The Impact of Mathematics in Shaping the Understanding of Nature and Humanity - BAYUG, JAYWARD (International Journal of Arts, Sciences and Education, 2022)
With the impact of mathematics in shaping the understanding of nature and humanity, the mathematics educators are concerned on the students’ level of proficiency in mathematics education. In this paper, it aims to investigate the understanding of the students on mathematics in nature and mathematics in humanity, and also the impact of this in the society. With result of the assessment of the Philippines on the math-science global assessment conducted by TIMSS 2019, this study analysed the impact of the result of the assessment to the Philippine education. With the analysis of this study, Mathematics educators was found to play the greatest role in facilitating the students’ understanding of nature and humanity through math.